The clinical and economic burden of patients with chronic liver disease and thrombocytopaenia receiving platelet transfusions during planned invasive procedures. Issue 5 (29th August 2019) - Brown, Robert S.; Bentley, Roy; Cai, Bin; Flamm, Steven L.; Kanakamedala, Hemanth; Lai, Jennifer; Marcella, Stephen; Muir, Andrew J.; Brown, Kimberly A.
Summary: Background: Platelet transfusions (PT) are the standard of care for thrombocytopaenia in patients with chronic liver disease (CLD) who are at risk for bleeding when undergoing planned invasive procedures (PIP). In addition to PTs having short‐term effectiveness, PTs are associated with complications (transfusion‐associated circulatory overload [TACO], transfusion‐related acute lung injury [TRALI] and increased healthcare resource utilisation [HCRU]). Objective: To characterise the clinical and economic burden among CLD patients who receive a PT for their PIP. Methods: A retrospective analysis was performed using MarketScan ® research databases. A PT‐related population that consisted of patients who received a PT for their PIP and a non‐PT‐related population diagnosed with thrombocytopaenia that did not receive a PT for their PIP were derived. Each PT‐related patient was matched with 1‐3 non‐PT‐related patients on factors predictive of severity of liver disease and increased HCRU. Results: After applying the inclusion criteria and patient‐matching, 210 patients were included in the PT‐related population and 564 patients were included in the non‐PT‐related population. PT‐related patients had an increase (mean increase: $11.1K; median increase: $2.1K) in payments received between admission date of the PIP‐related hospitalisation and 30 days after discharge. PT‐related patients also had a higher proportion of bleeding events (PT‐related: 32%; non‐PT‐related: 18%), TACO‐related complications (PT‐related: 23%; non‐PT‐related: 18%) and TRALI‐related complications (PT‐related: 19%; non‐PT‐related: 14%). Conclusion: PT‐related patients incurred substantially higher costs during and after their PIP‐related hospitalisation. Optimal management of thrombocytopaenia in the CLD population is critical in maintaining successful clinical and economic outcomes.